Principles for detecting suspicious activity and programs for analyzing suspicious activity using CCTV cameras - Rustemov, А.Б.; Kuzenbaev, Б.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The proposed article discusses the principles of detecting suspicious activity from the point of view of human logic and psychology, and also explores existing programs for analyzing suspicious activity using CCTV cameras. The main types of suspicious activity are considered, such as crowding, fast movement, penetration into a protected area and things left unattended, as well as methods and tools that can be used to detect them. The study of existing programs touches on the advantages and disadvantages of popular programs for analyzing suspicious activity through video surveillance, including discussing the concept of a program that could compete with other programs in this direction, introducing innovations, using the advantages of competitors and avoiding the disadvantages of rivals.